Keragaman dan kualitas konsumsi pangan pada remaja usia 15–17 tahun - Andra Vidyarini; Elia Nur Ayunin (ARGIPA (Arsip Gizi dan Pangan), 2022)
Nutritional problems in adolescents have increased from year to year and one of the causes is the low diversity and quality of consumption. The diversity and quality of consumption can be seen through the Individual Dietary Diversity Score and the Healthy Eating Index. This study was cross-sectional by looking at the diversity and quality of consumption of adolescents aged 15-17 years. The total subjects in this study amounted to 70 teenagers. This research was conducted online via google form and the results were analyzed using chi-square. The results showed that the diversity of the subject's food consumption was in the diverse and very diverse category with an average of 6. However, the quality was still not good whereas it was still in the bad and moderate categories with an average of 12,93. Analysis of the relationship between diversity and quality of food consumption showed that consumption diversity had a significant relationship with the quality of food consumption. These results indicated that the more diverse the food consumed, the better the quality of food consumption.